2022
DOI: 10.1021/jacs.2c00778
|View full text |Cite
|
Sign up to set email alerts
|

Cyanurate-Linked Covalent Organic Frameworks Enabled by Dynamic Nucleophilic Aromatic Substitution

Abstract: We report, for the first time, highly crystalline cyanurate-linked covalent organic frameworks synthesized via dynamic nucleophilic aromatic substitution. The high crystallinity is enabled by the bond exchange reaction (self-correction) between 2,4,6triphenoxy-1,3,5-triazine and diphenols via reversible S N Ar catalyzed by triazabicyclodecene. The CN-COFs contain flexible backbones that exhibit a unique AA′-stacking due to interlayer hydrogen bonding interactions. The isoreticular expansion study demonstrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…For Ton-COFs, the clear signals at 150 and 152 ppm correspond to the amide and triazine carbon atoms, respectively. 25,26 However, three signals at 167, 164, and 160 ppm are exhibited for Tol-COFs, which all pertain to the triazine carbon atoms. 27 It is conjectured that a division of the signal originated from the incomplete edge structure and/ or defects.…”
Section: Resultsmentioning
confidence: 99%
“…For Ton-COFs, the clear signals at 150 and 152 ppm correspond to the amide and triazine carbon atoms, respectively. 25,26 However, three signals at 167, 164, and 160 ppm are exhibited for Tol-COFs, which all pertain to the triazine carbon atoms. 27 It is conjectured that a division of the signal originated from the incomplete edge structure and/ or defects.…”
Section: Resultsmentioning
confidence: 99%
“…[28] The high chemical stability of the sp 3 atom-bridged arene cages enabled the introduction of functional groups by post-synthetic modification, [42][43][44][45] allowing the investigation as catalysts, [46] scaffolds for covalent/metalorganic frameworks (COFs/MOFs), [47,48] and porous organic crystals. [31,42,49,50] Although these methods have allowed the synthesis of various prismatic cages, the synthesis of a tetrahedral one has been limited to a thermodynamically controlled dynamic S N Ar reaction [51][52][53] that requires the slow addition of a substrate (2 hours). This reversible covalent bond formation made the resulting cage product chemically unstable.…”
Section: Methodsmentioning
confidence: 99%
“…For Fig. 13 Representative linkages for fabricating COFs with high stability or CO 2 capture performance: polyimide linkage, 210 imidazole linkage, 209 ester linkage, 211 arylamine linkage, 212 azine linkage, 213 1,4-dioxin or dithiine linkage, 214,215 ketoenamine linkage, 216 aminal linkage, 217 fused-ring linkage, 206 hydrazone Linkage, 218 benzofuran linkage, 219 triazine linkage, 220 CQC linkage, 221 CQC linkage, 222 amine linkage, 144 urea linkage, 223 Michael additionelimination, 224 pyrimidazole linkage, 225 benzoxazole or benzothiazole linkage, 226 tetrahydroquinoline linkage, 41 hydrazine-hydrazide linkage, 207 benzimidazole linkage, 227 phenazine linkage, 228 carbamate or thiocarbamate linkage, 229 benzimidazole linkage, 81 aminonitrile linkage, 230 quinoline linkage, 143 cyanurate Linkage, 202 piperazine linkage, 107 quinoline linkage, 231 triazine linkage, 232 azo linkage, 233 n-acylhydrazone linkage, 234 imidazopyridinium linkage, 235 4-carboxyl-quinoline linkage, 236 benzoxazine linkage, 237 propargylamine linkage, 238 buta-1,3-diene-linkage, 239 thieno[3,2-c]pyridine linkage, 240 and benzobisoxazole-vinylene linkage. …”
Section: Building Blocksmentioning
confidence: 99%
“…For example, Zhang and co-authors reported a cyanurate-linked COF through irreversible nucleophilic aromatic substitution between 2,4,6-triphenoxy-1,3,5-triazine and diphenols that can not only survive in the presence of an acid, oxidizing agent, and reducing agent, but also has good CO 2 adsorption capacity up to 50 cm 3 g −1 at 273 K and 1 bar. 202 However, other linkages, such as boroxine and boronate ester linkage, suffer from hydrolysis in the presence of water, hindering the application in practical CO 2 capture. As imine is one of the most reported linkages for constructing COFs, recently, another strategy is to use post-modification methods to improve the imine linkage stability and generate different properties.…”
Section: How To Design Future Cofs For Carbon Capture?mentioning
confidence: 99%